2015
DOI: 10.3109/21691401.2015.1115410
|View full text |Cite
|
Sign up to set email alerts
|

A strategic approach for rapid synthesis of gold and silver nanoparticles byPanax ginsengleaves

Abstract: The study highlights the synthesis of gold nanoparticles and silver nanoparticles by fresh leaves of Panax ginseng, an herbal medicinal plant. The reduction of auric chloride and silver nitrate led to the formation of gold and silver nanoparticles within 3 and 45 min, at 80°C, respectively. The developed methodology was rapid, facile, ecofriendly and the utmost significant is quite economical, which did not require subsequent processing for reduction or stabilization of nanoparticles. The nanoparticles were fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(85 citation statements)
references
References 29 publications
7
78
0
Order By: Relevance
“…This is due to surface plasmon resonance phenomenon of the electrons in the conduction band of silver. The UV-vis spectrometric analysis of the final reaction mixtures TCA-AgNP, TCA-AgNP-PI, Cinn-AgNP, and Cinn-AgNP-PI showed absorption peaks around 390-415 nm, which are the characteristic peaks for AgNPs ( Figure 5a) in agreement with previous studies with values around 412 nm [64,94]. Soni et al synthesized AgNP with cinnamomum zeylanicum and reported a broad peak at 480 nm [66].…”
Section: Discussionsupporting
confidence: 88%
“…This is due to surface plasmon resonance phenomenon of the electrons in the conduction band of silver. The UV-vis spectrometric analysis of the final reaction mixtures TCA-AgNP, TCA-AgNP-PI, Cinn-AgNP, and Cinn-AgNP-PI showed absorption peaks around 390-415 nm, which are the characteristic peaks for AgNPs ( Figure 5a) in agreement with previous studies with values around 412 nm [64,94]. Soni et al synthesized AgNP with cinnamomum zeylanicum and reported a broad peak at 480 nm [66].…”
Section: Discussionsupporting
confidence: 88%
“…Ginseng plants show many properties such as antimicrobial, antibacterial and antiviral properties. This plant was used for the synthesis of gold and silver nanoparticles [36]. These nanoparticles were formed by the reduction of auric chloride and silver nitrate, respectively, and they have been studied and found to be resistant toward biofilm produced by microbes.…”
Section: Panax Ginsengmentioning
confidence: 99%
“…25 FE-TEM was used to analyze the selected area (electron) diffraction (SAED) and fast Fourier transform (FFT) pattern of BSA-Rh2 NPs. 26 The hydrodynamic particle size distribution, polydispersity index, and zeta potential were analyzed using a DLS instrument at 25°C (Photal or Otsuka Electronics, Hirakata, Japan). The BSA-Rh2 NPs sample was dispersed in water, as a reference, a dispersive medium of pure water with a refractive index of 1.3328, viscosity of 0.8878, and dielectric constant of 78.3 was used.…”
Section: −1mentioning
confidence: 99%